O cenário produtivo e a representatividade dos rios Jacuí e Soturno para o município de Dona Francisca - RS - Dalla Favera, Alex (2006)
The goal of the work was the study of the transformations of the structure of agricultural production for two last decades in the municipal district of Dona Francisca- RS, as wall as the representativity of hidrical resources Rio Jacuí for this local. In first moment it used of the wide importance theoretical specific of the subject at issue, with the purpose basing the theoretical methodological development of the research. The second part of the research was related with the field work, where it used of applied interviews direct to producers, totalising 25, and the population in general total of 50. Thus was possible verify the transformations of Dona Francisca. The appreciation in set of the results allowed obtainment of the general square of situation of the agricultural sector and of the Rio Jacuí and Soturno in Dona Francisca, could evaluated the perspectives of development and the tendencies of this small portion of rural space gaucho.